The Use of Fillers in Spoken Discourse Video by Students at English Language Education Study Program of State University of Gorontalo - Dhea Wulandari Cahyo; Hasanuddin Fatsah; Zulkifli Tanipu (Transbahasa, 2025)
This study analyzes the Use of fillers in spoken discourse videos by students of the English Language Education Study Program at Gorontalo State University (UNG). The purpose is to identify the types of fillers used and the factors that influence their Use. This study uses a qualitative descriptive method with data collected through analysis of students' video assignments, interviews, and documentation. The results showed that the most frequently used fillers were unlexicalized (e.g.,